High-stability nano C-S-H crystal nucleus early strength agent and preparation method thereof

By adopting a composite system of dispersant A and dispersant B, the problems of stability and water-reducing agent usage in the prior art are solved, and high stability, early strength improvement and water-reducing agent usage are achieved. Effect.

CN119504172APending Publication Date: 2025-02-25CHINA TIESIJU CIVIL ENGINEERING GROUP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534555.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, when preparing nano C-S-H early strength agents with high stability, the design and use of dispersants are limited, resulting in agglomeration of nanoparticles, early strength increases, but the amount of water reducing agents increases, affecting concrete fluidity.

Method used

A composite system is adopted with two dispersant A and dispersant B, where dispersant A is prepared from conventional polyether monomers, and dispersant B is composed of a polymer prepared under the conditions of high molecular weight polyether and high acid ether ratio, through Synergistically improves the stability of nano C-S-H and reduces the amount of water reducing agent.

Benefits of technology

The high stability and early strength improvement of nano C-S-H early strength agents are achieved, while the amount of water reducing agents is reduced, and the flowability and subsequent strength of concrete are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111240600000091
    Figure BDA0005111240600000091
  • Figure BDA0005111240600000101
    Figure BDA0005111240600000101
  • Figure BDA0005111240600000111
    Figure BDA0005111240600000111
Patent Text Reader

Abstract

The invention provides a high-stability nano C-S-H crystal nucleus early strength agent and a preparation method thereof, and relates to the technical field of concrete admixtures. The invention relates to a high-stability nano C-S-H crystal nucleus early strength agent, which is prepared from the following components in parts by weight: 50 to 70 parts of dispersing agent A, 50 to 70 parts of dispersing agent B, 300 to 400 parts of water, 10 to 30 parts of NaOH aqueous solution, 0.1 to 1 part of defoaming agent, 200 to 400 parts of Ca (NO3) 2.4 H2O aqueous solution and 150 to 350 parts of Na2SiO3. 5H2O aqueous solution. The early strength agent is formed by compounding two dispersants, is good in stability and high in early strength, and can reduce the use amount of a water reducing agent when being applied to concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a high-stability nano CSH crystal nucleus early strength agent and a preparation method thereof. Background Art

[0002] Nano CSH / PCE is one of the hot research directions for improving the early strength of concrete in recent years. Its preparation method is as follows: the key technology for preparing the material by aqueous solution co-precipitation method is to separately add calcium source and silicon source solutions under the action of dispersant to obtain different nano CSH suspension solutions. The performance of nano CSH early strength agent depends on product stability, dispersant type, dosage, calcium-silicon ratio, mass concentration, etc. In order to prepare nano CSH early strength agent with better stability, the special dispersant commonly used for CSH early strength agent is a polymer after the molecular structure of polycarboxylic acid water reducer is redesigned. For example, patent CN113979661 discloses that unsaturated carboxylic acid, unsaturated amide and water are used as raw materials to prepare droplet A; reducing agent, chain transfer agent and water are used as raw materials to prepare droplet B; droplet A, droplet B and primer A are prepared into a special dispersant to prepare a nano calcium silicate with high stability and good early strength effect, wherein polyether macromonomer, unsaturated alcohol, unsaturated carboxylic acid, unsaturated amide The mass ratio of is 100: (1-3): (10-15): (2-4), the molecular weight of the polyether macromonomer is 5000-8000, the molecular weight of the monomer used in the special dispersant, the proportion of each material and the type of monomer are significantly different from those of the conventional water reducer. The conventional polycarboxylic acid water reducer mostly uses four carbon (methyl allyl polyethylene glycol ether), five carbon (isoprenol polyoxyethylene ether), six carbon (ethyleneoxyethyl polyethylene glycol ether) polyether with a molecular weight of 2400-3000, and the acid-ether ratio also needs to be controlled within a suitable range. The molar ratio is generally between 3:1 and 5:1 to have a good water reduction rate. The main function of the special dispersant prepared by the prior art is to stabilize the nano CSH particles from agglomeration. Its application in concrete is to use its seeding effect to achieve the effect of improving the early strength, promote the cement hydration of cement, and have a certain effect on the fluidity of concrete, but when used with a water reducer, it is usually necessary to increase the amount of the water reducer. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a high-stability nano CSH crystal nucleus early strength agent and a preparation method thereof.

[0004] The invention provides a high-stability nano CSH crystal nucleus early strength agent, comprising a dispersant A and a dispersant B;

[0005] The dispersant A comprises the following raw materials in parts by weight: 300-500 parts of polyether, 400-500 parts of water, 3-9 parts of sodium hypophosphite, 0.5-3 parts of catalyst, 0.5-3 parts of hydrogen peroxide, 40-70 parts of acrylic acid aqueous solution, and 150-250 parts of vitamin C aqueous solution.

[0006] The preparation method of the dispersant A comprises the following steps:

[0007] Add polyether, water, sodium hypophosphite, catalyst and hydrogen peroxide to the reaction kettle in sequence and stir evenly to obtain a mixture. At 30° C., add acrylic acid aqueous solution and vitamin C aqueous solution dropwise to the mixture. After the addition is completed, stir evenly to obtain dispersant A.

[0008] Preferably, the dropping time of the acrylic acid aqueous solution is 200 to 300 minutes, and the dropping time of the vitamin C aqueous solution is 250 to 350 minutes.

[0009] Preferably, the polyether is selected from one or more of isopentanol polyethylene glycol ether and methallyl polyethylene glycol ether.

[0010] Preferably, the molecular weight of the polyether is 2400-3000.

[0011] Preferably, the catalyst is a FeSO4·7H2O aqueous solution.

[0012] Preferably, the mass ratio of acrylic acid to water in the acrylic acid aqueous solution is (30-50):(10-20).

[0013] Preferably, the mass ratio of vitamin C to water in the vitamin C aqueous solution is (0.1-1):(150-250).

[0014] The dispersant B comprises the following raw materials in parts by weight: 300-450 parts of polyether, 300-450 parts of water, 1-5 parts of catalyst, 3-10 parts of hydrogen peroxide, 100-250 parts of mixed solution A, and 80-200 parts of mixed solution B.

[0015] The preparation method of the dispersant B comprises the following steps:

[0016] Polyether, water, catalyst and hydrogen peroxide are sequentially added into a reaction kettle and mixed evenly to obtain a mixture, mixed solution A and mixed solution B are simultaneously added dropwise into the mixture, and after the addition is completed, the mixture is stirred evenly to obtain a dispersant B.

[0017] Preferably, the dropwise addition time of the mixed solution A is 50 to 80 minutes.

[0018] Preferably, the dropwise addition time of the mixed solution B is 60 to 90 minutes.

[0019] Preferably, the polyether is selected from one or more of isopentenyl polyethylene glycol ether, vinyloxyethyl polyethylene glycol ether, and methallyl polyethylene glycol ether.

[0020] Preferably, the molecular weight of the polyether is 3000-6000.

[0021] Preferably, the mixed solution A comprises acrylic acid, mercaptopropionic acid, water and acrylamide; wherein the mass ratio of acrylic acid, mercaptopropionic acid, water and acrylamide is (50-70):(1-5):(100-150):(3-8).

[0022] Preferably, the molar ratio of acrylic acid to polyether in the mixed solution A is (8-13):1.

[0023] Preferably, the mixed solution B comprises vitamin C and water; wherein the mass ratio of vitamin C to water is (0.5-3): (100-150).

[0024] Preferably, the nano CSH crystal nucleus early strength agent further comprises water, NaOH aqueous solution, defoaming agent, Ca(NO3)2·4H2O aqueous solution, Na2SiO3·5H2O aqueous solution.

[0025] Preferably, the nano CSH crystal nucleus early strength agent comprises, by weight, 50 to 70 parts of dispersant A, 50 to 70 parts of dispersant B, 300 to 400 parts of water, 10 to 30 parts of NaOH aqueous solution, 0.1 to 1 part of defoaming agent, 200 to 400 parts of Ca(NO3)2·4H2O aqueous solution, and 150 to 350 parts of Na2SiO3·5H2O aqueous solution.

[0026] The present invention also proposes a method for preparing a high-stability nano CSH crystal nucleus early strength agent, comprising the following steps:

[0027] S1. Add dispersant A, dispersant B and water into the reaction kettle in sequence and stir evenly, then add NaOH aqueous solution to adjust the pH to 9-13, add defoamer and stir evenly to obtain a mixed material;

[0028] S2. Under high-speed dispersion conditions, Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution are simultaneously added to the mixed material. After the addition is completed, the mixture is stirred and aged to obtain a nano CSH crystal nucleus early strength agent.

[0029] In the S2, the initial reaction temperature is 25-35°C.

[0030] In the S2, the shear speed of high-speed dispersion is ≥20m / s.

[0031] In the S2, the dropping time is 1 to 2 hours.

[0032] In the S2, the aging time is 0.5 to 1 h.

[0033] The beneficial effects of the present invention are:

[0034] The early strength agent of the present invention is composited by two dispersants, dispersant A is a conventional polycarboxylate water reducer with a high water reducer rate prepared from a polyether monomer of a conventional molecular weight, which has a good dispersing effect on cement paste, but has a weak stabilizing effect on nano CSH; dispersant B is a high molecular polymer prepared by introducing ammonium acrylate and a polyether with a molecular weight of 3000 to 6000 under a high acid-ether ratio (8:1 to 13:1), which has a low water reduction rate as a water reducer, a high carboxyl density on the main chain, and a long side chain length, and has good stability for nano CSH. The dispersant of the present invention has dispersant A and dispersant B in a ratio of 50 to 70 parts by mass: 50 to 70 parts by mass, and the two play a synergistic role with each other, which has a better stability effect on nano CSH, and dispersant A can also play a water reducing effect, and the prepared nano early strength agent is applied in concrete, which not only improves the early strength, but also reduces the amount of water reducer used. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is described in detail through specific embodiments.

[0036] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0037] Example 1

[0038] A high-stability nano CSH crystal nucleus early strength agent comprises, by weight, 58.5 parts of dispersant A, 58.5 parts of dispersant B, 328 parts of water, 15 parts of 30wt% NaOH aqueous solution, 0.5 parts of organosilicon defoamer, 278 parts of 44.4wt% Ca(NO3)2·4H2O aqueous solution, and 254 parts of 40wt% Na2SiO3·5H2O aqueous solution.

[0039] The preparation method of the dispersant A comprises the following steps:

[0040] 400 parts of isopentanol polyoxyethylene ether with a molecular weight of 2400, 470 parts of water, 6.7 parts of sodium hypophosphite, 1.1 parts of 1.5wt% FeSO4·7H2O aqueous solution and 1.4 parts of hydrogen peroxide were sequentially added into a reaction kettle and stirred to obtain a mixture. At 30° C., 53.7 parts of 73.7wt% acrylic acid aqueous solution and 199.55 parts of 0.23wt% vitamin C aqueous solution were simultaneously added dropwise into the mixture, wherein the acrylic acid aqueous solution was added dropwise for 240 min, and the vitamin C aqueous solution was added dropwise for 270 min. After the addition was completed, the mixture was stirred for 30 min to obtain a dispersant A.

[0041] The preparation method of the dispersant B comprises the following steps:

[0042] 375 parts of methyl allyl polyethylene glycol ether with a molecular weight of 4000, 375 parts of water, 3.4 parts of 0.5wt% FeSO4·7H2O aqueous solution and 4.8 parts of hydrogen peroxide were added to a reaction kettle in sequence and mixed evenly to obtain a mixture; 59.46 parts of acrylic acid, 1.9 parts of mercaptopropionic acid, 106.4 parts of water and 4.2 parts of acrylamide were mixed evenly to obtain a mixed solution A; 0.96 parts of vitamin C and 112.5 parts of water were mixed evenly to obtain a mixed solution B; mixed solution A and mixed solution B were simultaneously added dropwise to the mixture, the dropping time of mixed solution A was 60 minutes, and the dropping time of mixed solution B was 70 minutes, and after the dropping was completed, the mixture was stirred for 30 minutes to obtain a dispersant B.

[0043] A method for preparing a high-stability nano CSH crystal nucleus early strength agent comprises the following steps:

[0044] S1. Add dispersant A, dispersant B and water into a reaction kettle in sequence and stir evenly, then add 32 wt % NaOH aqueous solution to adjust the pH to 12, add defoamer and stir evenly to obtain a mixed material;

[0045] S2. Under the initial reaction temperature of 25°C and high-speed dispersion conditions (shear rate ≥ 20ms), Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution were simultaneously added to the mixture for 90 minutes. After the addition was completed, the mixture was stirred and aged for 0.5 hours to obtain a nano CSH crystal nucleus early strength agent.

[0046] Example 2

[0047] A high-stability nano CSH crystal nucleus early strength agent comprises, by weight, 68.5 parts of dispersant A, 50 parts of dispersant B, 328 parts of water, 15 parts of 30wt% NaOH aqueous solution, 0.7 parts of organosilicon defoamer, 250 parts of 44.4wt% Ca(NO3)2·4H2O aqueous solution, and 260 parts of 35wt% Na2SiO3·5H2O aqueous solution.

[0048] The preparation method of the dispersant A comprises the following steps:

[0049] 360 parts of isopentanol polyoxyethylene ether with a molecular weight of 3000, 470 parts of water, 5 parts of sodium hypophosphite, 1.5 parts of 1.5 wt% FeSO4·7H2O aqueous solution and 2.6 parts of 27.5 wt% hydrogen peroxide were added to a reaction kettle in sequence and stirred to obtain a mixture. At 30° C., 60 parts of 73.7 wt% acrylic acid aqueous solution and 199.55 parts of 0.23 wt% vitamin C aqueous solution were simultaneously added dropwise to the mixture, wherein the acrylic acid aqueous solution was added dropwise for 240 min, and the vitamin C aqueous solution was added dropwise for 270 min. After the addition was completed, the mixture was stirred for 30 min to obtain a dispersant A.

[0050] The preparation method of the dispersant B comprises the following steps:

[0051] 375 parts of ethyleneoxyethyl polyethylene glycol ether with a molecular weight of 5000, 375 parts of water, 4.5 parts of 0.5wt% FeSO4·7H2O aqueous solution and 6.2 parts of hydrogen peroxide are sequentially added into a reaction kettle and mixed evenly to obtain a mixture; 59.46 parts of acrylic acid, 1.9 parts of mercaptopropionic acid, 106.4 parts of water and 5 parts of acrylamide are mixed evenly to obtain a mixed solution A; 0.64 parts of vitamin C and 112.5 parts of water are mixed evenly to obtain a mixed solution B; mixed solution A and mixed solution B are simultaneously added dropwise to the mixture, the dropping time of mixed solution A is 60 minutes, and the dropping time of mixed solution B is 70 minutes, and after the dropping is completed, stirring is performed for 30 minutes to obtain a dispersant B.

[0052] A method for preparing a high-stability nano CSH crystal nucleus early strength agent comprises the following steps:

[0053] S1. Add dispersant A, dispersant B and water into a reaction kettle in sequence and stir evenly, then add 32 wt % NaOH aqueous solution to adjust the pH to 12, add defoamer and stir evenly to obtain a mixed material;

[0054] S2. Under the initial reaction temperature of 25°C and high-speed dispersion conditions (shear rate ≥ 20ms), Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution were simultaneously added to the mixture for 90 minutes. After the addition was completed, the mixture was stirred and aged for 0.5 hours to obtain a nano CSH crystal nucleus early strength agent.

[0055] Example 3

[0056] A high-stability nano CSH crystal nucleus early strength agent comprises, by weight, 50 parts of dispersant A, 70 parts of dispersant B, 328 parts of water, 15 parts of 30wt% NaOH aqueous solution, 0.5 parts of organic silicon defoamer, 260 parts of 44.4wt% Ca(NO3)2·4H2O aqueous solution, and 280 parts of 35wt% Na2SiO3·5H2O aqueous solution.

[0057] The preparation method of the dispersant A comprises the following steps:

[0058] 460 parts of isopentanol polyoxyethylene ether with a molecular weight of 2900, 470 parts of water, 6.3 parts of sodium hypophosphite, 1.8 parts of 1.5wt% FeSO4·7H2O aqueous solution and 1.9 parts of 27.5wt% hydrogen peroxide were added to a reaction kettle in sequence and stirred to obtain a mixture. At 30°C, 60 parts of 73.7wt% acrylic acid aqueous solution and 199.55 parts of 0.23wt% vitamin C aqueous solution were simultaneously added dropwise to the mixture, wherein the acrylic acid aqueous solution was added dropwise for 240 min, and the vitamin C aqueous solution was added dropwise for 270 min. After the addition was completed, the mixture was stirred for 30 min to obtain a dispersant A.

[0059] The preparation method of the dispersant B comprises the following steps:

[0060] 375 parts of ethyleneoxyethyl polyethylene glycol ether with a molecular weight of 6000, 375 parts of water, 4.5 parts of 0.5wt% FeSO4·7H2O aqueous solution and 6.2 parts of hydrogen peroxide are sequentially added into a reaction kettle and mixed evenly to obtain a mixture; 59.46 parts of acrylic acid, 1.9 parts of mercaptopropionic acid, 106.4 parts of water and 5 parts of acrylamide are mixed evenly to obtain a mixed solution A; 0.64 parts of vitamin C and 112.5 parts of water are mixed evenly to obtain a mixed solution B; mixed solution A and mixed solution B are simultaneously added dropwise to the mixture, the dropping time of mixed solution A is 60 minutes, and the dropping time of mixed solution B is 70 minutes, and stirring is performed for 30 minutes after the dropping is completed to obtain a dispersant B.

[0061] A method for preparing a high-stability nano CSH crystal nucleus early strength agent comprises the following steps:

[0062] S1. Add dispersant A, dispersant B and water into a reaction kettle in sequence and stir evenly, then add 32 wt % NaOH aqueous solution to adjust the pH to 12, add defoamer and stir evenly to obtain a mixed material;

[0063] S2. At an initial reaction temperature of 25°C and high-speed dispersion conditions (shear rate ≥ 20ms), Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution were simultaneously added to the mixture for 90 minutes. After the addition was completed, the mixture was stirred and aged for 1 hour to obtain a nano CSH crystal nucleus early strength agent.

[0064] Comparative Example 1

[0065] The early strength agent is a commercially available nano CSH early strength agent with a solid content of 21%, a pH value of 9.8, a calcium-silicon molar ratio of 1.5:1, and a nano early strength agent particle size of 279 nm.

[0066] Comparative Example 2

[0067] A nano CSH crystal nucleus early strength agent comprises, by weight, 110 parts of dispersant B, 328 parts of water, 15 parts of 30wt% NaOH aqueous solution, 0.5 parts of organosilicon defoamer, 260 parts of 44.4wt% Ca(NO3)2·4H2O aqueous solution, and 280 parts of 35wt% Na2SiO3·5H2O aqueous solution.

[0068] The preparation method of the dispersant B is the same as that in Example 3.

[0069] A method for preparing a nano CSH crystal nucleus early strength agent comprises the following steps:

[0070] S1. Add dispersant B and water into a reactor in sequence and stir evenly, then add 32 wt % NaOH aqueous solution to adjust the pH to 12, add defoamer and stir evenly to obtain a mixed material;

[0071] S2. At an initial reaction temperature of 25°C and high-speed dispersion conditions (shear rate ≥ 20ms), Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution were simultaneously added to the mixture for 90 minutes. After the addition was completed, the mixture was stirred and aged for 1 hour to obtain a nano CSH crystal nucleus early strength agent.

[0072] Comparative Example 3

[0073] A nano CSH crystal nucleus early strength agent comprises, by weight, 120 parts of dispersant A, 328 parts of water, 15 parts of 30wt% NaOH aqueous solution, 0.5 parts of organic silicon defoamer, 260 parts of 44.4wt% Ca(NO3)2·4H2O aqueous solution, and 280 parts of 35wt% Na2SiO3·5H2O aqueous solution.

[0074] The preparation method of the dispersant A is the same as the preparation method of the dispersant A in Example 3.

[0075] A method for preparing a nano CSH crystal nucleus early strength agent comprises the following steps:

[0076] S1. Add dispersant A and water into a reaction kettle in sequence and stir evenly, then add 32 wt % NaOH aqueous solution to adjust the pH to 12, add defoamer and stir evenly to obtain a mixed material;

[0077] S2. Under the initial reaction temperature of 25°C and high-speed dispersion conditions (shear rate ≥ 20ms), Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution were simultaneously added to the mixture for 90 minutes. After the addition was completed, the mixture was stirred and aged for 1.5 hours to obtain a nano CSH crystal nucleus early strength agent.

[0078] Test Example 1

[0079] Nano early strength agent stability test: (1) Take 10mL of the prepared nano CSH crystal core early strength agent in a centrifuge tube with a cap, centrifuge at a speed of 10000r / min for 6min, then take out the centrifuge tube and observe the stratification of the solution. The more sediment at the bottom, the worse the stability of the nano CSH. (2) Place the nano CSH crystal core early strength agent in a 100mL stoppered measuring cylinder and observe the stratification for 1-3 months at room temperature and indoor environment. The test results are shown in Table 1.

[0080] Table 1 Stability test results of the early strength agent in the examples and comparative examples

[0081]

[0082] From the data in Table 1, it can be seen that the nano early strength agent and the commercial early strength agent prepared by using two dispersants in Examples 1 to 3 have good stability, and no stratification and precipitation phenomenon is found under centrifugal and static conditions. However, Comparative Example 2 uses only dispersant B on the basis of Example 3. The dispersant has a strong stabilizing effect on the nano-scale CSH particles, and there is a small amount of precipitation under centrifugal and static conditions. With the extension of the static time, the amount of precipitation tends to increase, and the stabilizing effect is not as good as that of Example 3 using both dispersants A and dispersant B. Comparative Example 3 uses only dispersant A on the basis of Example 3. The dispersant has obvious precipitation under both evaluation conditions, and has been basically completely precipitated after standing for 1 day.

[0083] Test Example 2

[0084] The above-mentioned early strength agent is applied to C30 shotcrete, and the concrete mix ratio (kg / m 3) is cement: sand: stone (5-10mm): water = 450:862:863:175. The cement used was ordinary Portland cement (PO 42.5), the sand used was river sand with a fineness modulus of 2.5, the gravel used was small stones (5-10mm), the water was tap water, the water reducer was a polycarboxylic acid high-performance water reducer (RAWY-101 standard type) produced by Anhui China Railway Engineering Materials Technology Co., Ltd., the accelerator was an alkali-free liquid accelerator (ZT-WS01) produced by Anhui China Railway Engineering Materials Technology Co., Ltd., the accelerator dosage was fixed at 8% of the cement mass, the early strength agent dosage was 5%, the water reducer dosage was the dosage of the concrete under the same slump conditions, the order of mixing concrete was to mix cement, sand, stone and other materials, then add the nano early strength agent, water reducer and water at the same time and stir for 3 minutes, evaluate the fluidity and state of the concrete, simulate the on-site construction, let the concrete stand for 1 hour, then add the accelerator and stir evenly to form the test block, and carry out standard curing in the curing room, starting from the time when the accelerator was added, according to the "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" GB / T 50081 tested the 8h compressive strength of concrete. The test results are shown in Table 2.

[0085] The difference between the blank test example and the example is that the dosage of the early strength agent is 0 and the dosage of the water reducing agent is 1.4%, and the rest is the same as the example.

[0086] Table 2 Performance evaluation of the early strength agent in the embodiments and comparative examples in shotcrete

[0087]

[0088]

[0089] It can be seen from the data in Table 1 that the early strength agent prepared by the present invention is a nano CSH gel, which has strong fluidity, no precipitation, a particle size of 350-450nm, good stability, and is easy to store at room temperature. The early strength agent prepared using dispersant A and dispersant B has a high water reduction rate while having high early strength. The use of water reducer can be reduced, and the workability of concrete can be effectively adjusted at the same time. It can be seen from the data of comparative example 1 and the embodiment that although the early strength agent on the market can improve the early strength, the water reduction rate is low and the concrete state cannot be improved. It can be seen from the data of comparative example 2 and the embodiment that, compared with the embodiment, the sample produced by comparative example 2 also has no obvious water reduction rate, and the early strength growth after using the embodiment sample in the shotcrete has an absolute advantage; it can be seen from the data of comparative example 3 and the embodiment that the comparative example 3 sample has no early strength effect; it can be seen from the data of the blank sample and the embodiment that the nano early strength agent has an ideal positive effect on the early strength improvement of shotcrete and the concrete state.

[0090] Test Example 3

[0091] The above-mentioned early strength agent is applied to the segment concrete, and the concrete mix ratio (unit: kg / m 3 ): cement: fly ash: sand: stone: water = 350:95:703:1147:146, cement is China Resources Fengkai P·O 42.5 cement, fly ash is second grade; sand is river sand with a fineness modulus of 2.7 and a mud content of 1.2%; the needle-like content of gravel is 5.5%, the crushing value is 4%, and the continuous gradation of 5-20mm. When mixing concrete, nano early strength agent and water reducer are added at the same time. According to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" GB / T 50081, its 6h strength (steaming 4h), 1d strength (steaming 4h), 4d strength, and 9d strength (steaming 4h) are tested. The test results are shown in Table 3. The water reducer is a polycarboxylic acid high-performance water reducer (RAWY-101 early strength type) from Anhui China Railway Engineering Materials Technology Co., Ltd.

[0092] Comparative Example 4

[0093] The difference between the test example of comparative example 4 and the embodiment is that the dosage of the early strength agent is 0 and the dosage of the water reducing agent is 2.4%, see Table 3 for details, and the rest is the same as the embodiment.

[0094] Comparative Example 5

[0095] The difference between the test example of comparative example 5 and the embodiment is that the dosage of the early strength agent is 0, the water reducing agent is 0.1% triethanolamine, and the dosage of the water reducing agent is 2.4%, see Table 3 for details, and the rest is the same as the embodiment.

[0096] Table 3 Performance evaluation of the early strength agent in the embodiment and the comparative example in the segment concrete

[0097]

[0098] It can be seen from the data in Table 2 that the use of the nano CSH crystal nucleus early strength agent of the present invention can not only effectively improve the early strength, reduce the amount of water reducing agent used, and does not affect the subsequent strength, and performs well in concrete. It can be seen from the data of Comparative Example 1, Comparative Example 2 and the embodiment that the nano early strength agent provided by the present invention has obvious advantages in improving the early strength of the pipe segment, and can reduce the amount of water reducing agent used while using it; it can be seen from the data of Comparative Example 3 and the embodiment that although the dispersant used in Comparative Example 3 has a high water reduction rate, it has a poor stabilizing effect on the nano early strength agent, and the prepared early strength agent has no effect on improving the early strength of the pipe segment concrete. It can be seen from the data of Comparative Example 5 and the embodiment that although triethanolamine can effectively improve the early strength of concrete, it has a little negative effect on the subsequent strength of concrete.

[0099] In summary, the early strength agent provided by the present invention has good stability and high early strength, and its application in concrete can reduce the amount of water reducing agent without affecting the subsequent strength.

[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-stability nano CSH crystal nucleus early strength agent, characterized in that: The invention comprises dispersant A and dispersant B; the dispersant A comprises the following raw materials in parts by weight: 300-500 parts of polyether, 400-500 parts of water, 3-9 parts of sodium hypophosphite, 0.5-3 parts of catalyst, 0.5-3 parts of hydrogen peroxide, 40-70 parts of acrylic acid aqueous solution, and 150-250 parts of vitamin C aqueous solution.

2. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The preparation method of the dispersant A comprises the following steps: adding polyether, water, sodium hypophosphite, a catalyst and hydrogen peroxide into a reaction kettle in sequence and stirring to obtain a mixture; simultaneously adding an acrylic acid aqueous solution and a vitamin C aqueous solution to the mixture at 30° C.; stirring to obtain the dispersant A after the addition is completed.

3. The nano CSH crystal nucleus early strength agent according to claim 2, characterized in that: The dropping time of the acrylic acid aqueous solution is 200 to 300 minutes, and the dropping time of the vitamin C aqueous solution is 250 to 350 minutes.

4. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The polyether is selected from one or more of isopentanol polyethylene glycol ether and methyl allyl polyethylene glycol ether; the molecular weight of the polyether is 2400-3000.

5. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The mass ratio of acrylic acid to water in the acrylic acid aqueous solution is (30-50):(10-20); the mass ratio of vitamin C to water in the vitamin C aqueous solution is (0.1-1):(150-250).

6. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The dispersant B comprises the following raw materials in parts by weight: 300-450 parts of polyether, 300-450 parts of water, 1-5 parts of catalyst, 3-10 parts of hydrogen peroxide, 100-250 parts of mixed solution A, and 80-200 parts of mixed solution B. The preparation method of the dispersant B comprises the following steps: adding polyether, water, catalyst, and hydrogen peroxide to a reaction kettle in sequence and mixing them evenly to obtain a mixture, simultaneously dripping the mixed solution A and the mixed solution B into the mixture, and stirring evenly after the dripping is completed to obtain the dispersant B.

7. The nano CSH crystal nucleus early strength agent according to claim 6, characterized in that: The polyether is selected from one or more of isopentenyl polyethylene glycol ether, vinyloxyethyl polyethylene glycol ether, and methallyl polyethylene glycol ether; the molecular weight of the polyether is 3000-6000; the mixed solution A comprises acrylic acid, mercaptopropionic acid, water, and acrylamide; wherein the mass ratio of acrylic acid, mercaptopropionic acid, water, and acrylamide is (50-70):(1-5):(100-150):(3-8); the mixed solution B comprises vitamin C and water; wherein the mass ratio of vitamin C to water is (0.5-3):(100-150).

8. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The nano CSH crystal nucleus early strength agent also includes water, NaOH aqueous solution, defoamer, Ca(NO3)2·4H2O aqueous solution, and Na2SiO3·5H2O aqueous solution.

9. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The nano CSH crystal nucleus early strength agent comprises, by weight, 50 to 70 parts of dispersant A, 50 to 70 parts of dispersant B, 300 to 400 parts of water, 10 to 30 parts of NaOH aqueous solution, 0.1 to 1 part of defoaming agent, 200 to 400 parts of Ca(NO3)2·4H2O aqueous solution, and 150 to 350 parts of Na2SiO3·5H2O aqueous solution.

10. A method for preparing the high-stability nano CSH crystal nucleus early strength agent according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add dispersant A, dispersant B and water into the reaction kettle in sequence and stir evenly, then add NaOH aqueous solution to adjust the pH to 9-13, add defoamer and stir evenly to obtain a mixed material; S2. Under high-speed dispersion conditions, Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution are simultaneously added to the mixed material. After the addition is completed, the mixture is stirred and aged to obtain a nano CSH crystal nucleus early strength agent.